新加坡青年双语者受英汉双向干扰的语言产出特征研究 = An investigation of language interference based on the features of oral production of young bilingual Singaporeans - 林恩盛 Lim, Derrick En Sheng (Nanyang Technological University, 2021)
在语言环境庞杂的新加坡，有九成的国人在家中同时以英语和母语作为沟通语言。当人们的语言产出不断在两个或以上的语言之间切换时，就会出现语言干扰的现象。本文从语言干扰的两大层面 – 语际迁移及语码转换，探讨英至汉、汉至英的双向干扰特征。针对从小接受本地双语教育的青年人，本研究分析30名参与者所提供的口语语料，并归纳出干扰的类别及导因。最后，本文以上述研究发现为基础，给我国的华文教学提供参考建议。Singapore is a multi-lingual society, with most of the population speaking English and Mother Tongue frequently in their daily lives. As a result, language interference between these two languages is an unavoidable phenomenon. This study examines the causes and features of English-Mandarin and Mandarin-English interference from two core aspects – code-switching and inter-lingual transfer, with a target group of youths who have been through Singapore’s bilingual education system. This paper analyses first-hand speech data from 30 participants, to uncover the types of interference embedded and the factors behind these occurrences. With the above information, suggestions to improve the teaching of Chinese language in local schools are also proposed in the final chapter.